2015
DOI: 10.1001/jamaophthalmol.2015.1760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Behavioral Intervention on Dilated Fundus Examination Rates in Older African American Individuals With Diabetes Mellitus

Abstract: IMPORTANCE African American individuals are at high risk of diabetes mellitus and diabetic retinopathy but have suboptimal rates of dilated fundus examinations (DFEs). Early intervention is crucial for the prevention of diabetic retinopathy in this high-risk population. OBJECTIVE To test the efficacy of behavioral activation for diabetic retinopathy prevention on rates of DFEs in older African American individuals with diabetes mellitus. DESIGN, SETTING, AND PARTICIPANTS Masked randomized clinical trial at 2 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
1
27
0
5
Order By: Relevance
“…The number of sources (or amount of exposure) is important, but so is the quality and accuracy of these sources of eye health information to increasing appropriate screening among those with diabetes. Weiss et al 40 found that when older African-Americans with diabetes underwent a behavioral intervention providing sources of information such as educational pamphlets, online information, and ophthalmology contact information, they were more likely to have a dilated eye examination within the following 6 months compared to those not receiving the intervention. Primary healthcare providers must be a key source of eye health information to their patients with diabetes, and they must also actively refer and encourage their patients to seek annual exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of sources (or amount of exposure) is important, but so is the quality and accuracy of these sources of eye health information to increasing appropriate screening among those with diabetes. Weiss et al 40 found that when older African-Americans with diabetes underwent a behavioral intervention providing sources of information such as educational pamphlets, online information, and ophthalmology contact information, they were more likely to have a dilated eye examination within the following 6 months compared to those not receiving the intervention. Primary healthcare providers must be a key source of eye health information to their patients with diabetes, and they must also actively refer and encourage their patients to seek annual exams.…”
Section: Discussionmentioning
confidence: 99%
“…When African-Americans with diabetes were given an educational intervention regarding the importance of eye care, the uptake of screening for diabetic retinopathy increased over the following 6 months compared to African-Americans who did not receive this treatment. 40 In summary, health promotion and education strategies that stress the importance of annual dilated eye examinations among Hispanics/Latinos with diabetes may affect a change in the number of Hispanics/Latinos who are examined, ultimately decreasing the burden of visual impairment and blindness secondary to diabetic retinopathy. Healthcare providers should play a key role in educating their patients with diabetes of the need for annual examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five RCTs, four (80%) adequately described their randomization sequence (Bond et al, 2010 -Reid et al, 2018), blinding of study per-sonnel was not described; all were rated as either high or unclear. For the attrition bias assessment, only two studies (40%) were free from frequent missing data (Nowlan et al, 2015;Weiss et al, 2015). In the three remaining studies (Bond et al, 2010;Taveira et al, 2011;Markle-Reid et al, 2015, 2018, no information was provided concerning the attrition rate or reasons for missing data.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In the three remaining studies (Bond et al, 2010;Taveira et al, 2011;Markle-Reid et al, 2015, 2018, no information was provided concerning the attrition rate or reasons for missing data. Lastly, for the selective reporting assessment, one study (20%) provided a study protocol (Weiss et al, 2015). The other studies either provided insufficient information, or the study protocol could not be located.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Considering poor adherence as a deleterious health behavior may encourage more researchers and clinicians to use techniques from the literature on behavior change as others have already done. 7 The indirect costs of clinical encounters are also noted as a possible challenge not mitigated in the present study, and some groups have explored financial incentives for retinopathy screening. 8 What is clear is that while finding diabetic retinopathy is a great start for ocular telehealth, it is far from sufficient to prevent vision loss.…”
mentioning
confidence: 90%